The man with the strange head and other early science fiction stories - Breuer, Miles John, 1889-1945.; Page, Michael R., 1967- (Lincoln : University of Nebraska Press, 2008)
A collection of science-fictional stories and essays written by Miles J. Breuer in the early twentieth century, including "Paradise and Iron," "The Gostak and the Doshes," "Mechanocracy, "The Future of Scientification," and more.
The man with the strange head, Amazing stories, January 1927 -- The appendix and the spectacles, Amazing stories, December 1928 -- The Gostak and the Doshes, Amazing stories, March 1930 -- Paradise and iron, Amazing stories quarterly, Summer 1930 -- A problem in communication, Astounding stories, September 1930 -- On board the martian liner, Amazing stories, March 1931 -- Mechanocracy, Amazing stories, April 1932 -- The finger of the past, Amazing stories, November 1932 -- Millions for defense, Amazing stories, March 1935 -- Mars colonizes, Marvel tales, Summer 1935 -- The oversight, Comet stories, December 1940 -- Appendix 1 : The future of scientifiction, Amazing stories quarterly, Summer 1929 -- Appendix 2: Selected letters.
Includes bibliographical references.
Adult.
Adult
Keywords: Breuer, Miles John, -- 1889-1945 -- Correspondence; Breuer, Miles John, -- 1889-1945 -- Correspondence; Short stories; Science fiction